Student's Belief Of Reading Material Used In Vocational High School Textbook - Hamidah, Mimi; Djatmika, Djatmika; Suparno, Suparno (International Journal of Educational Research & Social Sciences, 2024)
Reading text is one of the learning materials in English subjects providing information that supports the achievement of learning goals. This study aims to find out students’ beliefs about reading material in a vocational high school textbook. the participants were gained randomly from the fourteen students of a vocational high school in Lampung province. To collect the students’ beliefs, the researcher used a questionnaire adopted from Horwitz (1989) . The results of the questionnaire show that the highest score of student’s belief was “Language Learning and Motivation” (96%), followed by “Language Learning and Communication Strategy” (85%), “Belief of Language Aptitude” (73%), “Belief of Nature Language Learning” (70%), and “Difficulty of Language Learning” (69%).